Influence of COVID-19 on cardiac clinical trials: an observational study from clinical trials registry India - Saradha, S.; P. R., Kamalam; R. , Arunkumar; Indhra, P. (International Journal of Clinical Trials, 2023)
Background: Clinical trials on drugs for cardiac diseases becomes essential as coronary artery disease is the most common cause of death globally. This study observes if COVID-19 has influenced the number and pattern of cardiac trials conducted prior to and during COVID-19 from clinical trial registry of India web portal. Methods: The CTRI website was searched for the key words “myocardial infarction”, “heart failure”, “cardiac arrhythmia”, “myocarditis” and “pulmonary embolism” and the trials registered were reviewed. Data was collected for every trial registered from 1st January 2019 to 16th April 2021. Results: 156 Clinical trials were registered in the specified period. Of which 104 were on myocardial infarction, 24 on pulmonary embolism, 13 on cardiac arrhythmia, 9 on cardiac failure and 6 on myocarditis. Among the 156 trials, 98 were observational, 53 were interventional and 5 Post marketing surveillance type. 83% of the interventional studies were randomized controlled trials. Karnataka had the maximum number of trials registered 57, followed by Delhi 37 trials. 135 trials were done in India alone and 21 trials involved other countries as well. Among the interventions, 25 were drugs, 19 medical devices, 2 cardiac rehabilitations, 2 based on Yoga, 95 trials mentioned their intervention as NA and remaining 13 were adjuvant, standard treatment, physiotherapy, homeopathy and others. Conclusions: It was observed that COVID-19 pandemic did not have an influence on the conduct and pattern of cardiac trials in India.